STRUKTUR NARATIF DALAM NOVEL NARASI PERIHAL AYAH KARYA JAQUENZA EDEN - Laode Hamdar; Irianto Ibrahim; Rachman (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to describe the narrative structure of Jaquenza Eden’s novel Narasi Perihal Ayah by applying Tzvetan Todorov’s narrative theory. This research employs a descriptive qualitative method with a narrative analysis approach. The data consist of textual quotations representing the stages of the storyline: equilibrium, disruption, recognition, repair, and equilibrium again. The findings reveal that the novel portrays the emotional journey of a young boy named Ekal in coping with the loss of both his parents. The equilibrium stage is depicted through Ekal’s harmonious life with his mother, disruption occurs when he experiences loss and social pressure, recognition emerges as he realizes the painful reality, repair takes place through writing and self-reflection, and equilibrium again is achieved when Ekal finally accepts his situation and finds a new balance in life. Therefore, the novel not only presents a story of loss but also highlights a touching and profound process of emotional healing.